The Bonding Mechanism and Experimental Verification of Pilger Hot Rolling Clad Tube - Zonglin He; Zhibing Chu; Yuanhua Shuang; Yujun Gou (Advances in Materials Science and Engineering)
In this paper, we focus on the bonding mechanism of bimetallic clad tube because of its low cost and comprehensive properties. The numerical simulation and the experiment are carried out from the diffusion behavior of carbon atoms in the metallurgical bonding process. Based on the dislocation density model of Kocks, the tube billets are rolled by pilger hot rolling; the outer tube is 06Cr19Ni10 stainless steel, the inner tube is Q235 carbon steel, and the wall thickness ratio is 1 : 1. The research shows that the diffusion ability of carbon atoms mainly depends on the degree of the plastic strain in the stainless steel hot rolling process; there is positive correlation between the thickness of bonding carburized layer and the dislocation density produced by plastic deformation of stainless steel. The thickness difference of circumferential carburized layer in the deformation zone is larger than that near the finishing zone. Furthermore, a lot of contaminants cannot be completely metallurgically bonded between 20% and 30% reduction ratios; the contaminants near the bonding layer are refined and completely bonded metallurgically between 30% and 60% reduction ratios; the contaminants are further refined above 60% to 70% reduction ratio.